Paying the Price of Principle - Fudge, Judy (Labour / Le Travail, 1999)
Discusses the socio-political context of the Canadian Human Rights Tribunal's ruling regarding the pay equity complaint of the Public Service Alliance of Canada. The complaint was upheld, but the federal government filed an appeal. Argues for a new understanding of the labour market to counter the devisiveness of the prevailing neo-classical model.